2011
DOI: 10.1097/jto.0b013e3182295745
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of p16 Expression, Gene Status, and Promoter Hypermethylation In Surgically Resected Non-small Cell Lung Carcinomas

Abstract: Our comprehensive data would be compatible with a two-step process leading to loss of p16 expression in NSCLC. Hypermethylation of the promoter region may represent an early event, followed by heterozygous deletion of the p16 locus. Because of the possibility of detection of hypermethylated gene regions, these data may lead to the identification of specific patient subgroups more likely to benefit from upcoming demethylating treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
3
44
0
1
Order By: Relevance
“…Molecules involved in the cell cycle have often been reported as prognostic markers and although the cell cycle also seems to offer potential anticancer targets, such strategies are not yet routinely established [34,35,36,37]. This review summarizes the importance and recent findings concerning the cell cycle in NSCLC and discusses the prognostic and predictive aspects as well as the challenge of therapeutic approaches.…”
Section: Symptoms Prognosis and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules involved in the cell cycle have often been reported as prognostic markers and although the cell cycle also seems to offer potential anticancer targets, such strategies are not yet routinely established [34,35,36,37]. This review summarizes the importance and recent findings concerning the cell cycle in NSCLC and discusses the prognostic and predictive aspects as well as the challenge of therapeutic approaches.…”
Section: Symptoms Prognosis and Managementmentioning
confidence: 99%
“…Furthermore, cyclin D1 overexpression correlated with p16 loss and RB inactivation and the overall survival of patients with the combination of cyclin D1 overexpression and loss of p16 tended to show a rapid decline [59]. Our own observations of a multitude of cell cycle markers in a comparably large cohort (405 cases) of surgically resected NSCLC revealed that cyclin D1 overexpression is associated with the overexpression of cyclin D3, p27 (nuclear), p21 and the loss of p16 [36,37]. The only independent prognostic parameters by multivariable analysis were the overexpression of cyclin D1 and the loss of p16, both indicating poor overall survival [36,37].…”
Section: Cyclins In Nsclcmentioning
confidence: 99%
“…63 Several genes that have been identifi ed, including CDKN2A , FHIT , APC , p16 , and RASSF1A , appear to be commonly methylated. [64][65][66][67] Methylated genes may be detected using several techniques. The majority of early studies used technologies such as methylation-specifi c PCR and restriction landmark genomic scanning, which are targeted to specifi c genomic regions and candidates.…”
Section: Methylationmentioning
confidence: 99%
“…Повышенная экспрессия HDACs может привести к глушению транскрипции генов и аберрантной транскрипции из-за измененной экспрессии / мутации генов, кодирующих гистонаце-тилтрансферазу (HAT), HDAC-ферменты или их свя-зывающих партнеров, и тесно сопряжена с канцеро-генезом. Это происходит при многих злокачественных опухолях у человека, указывая на то, что активность аберрантного эпигенетического ацетилирования свя-зана с развитием рака [44][45][46]. Полагают, что после-довательные стадии ЭМП и мезенхимально-эпители-ального перехода, происходящие в процессе опухолевой прогрессии, могут быть обратимыми и свя-заны с эпигенетическими изменениями.…”
Section: экспериментальные статьиunclassified